Penerapan Lubang Resapan Biopori Di Desa Sukunan - Muhammad Rondi; Dodit Ardiatma (DPPM Universitas Pelita Bangsa, 2022)
Population growth has an impact on increasing the volume of household waste. The bad effects include the environment being dirty and garbage thrown into the gutter. The threat of flooding in the rainy season and drought in the dry season will also occur. The amount of household organic waste and the reduced availability of ground water in Sukunan Hamlet. Biopori Infiltration Hole is an effective and environmentally friendly technology to overcome flooding by increasing water absorption, converting organic waste into compost. The purpose of this practical work is to know the process of making biopori, to know the application of biopori, and to know the benefits of biopori in Sukunan Hamlet. The method used in this practical work is descriptive, data collection and direct observation to the field. The data collected consists of primary data and secondary data. The location of the practical work took place in Sukunan Hamlet, Banyuraden Village, Gamping District, Sleman Yogyakarta. The process of making biopore infiltration holes from start to finish includes the preparation of the necessary equipment, supplies and biopore materials. After making the biopore infiltration hole has been completed. Biopore infiltration holes must be treated so that their quality is maintained and can function properly. Applications of Biopori Infiltration Holes in Sukunan Hamlet are placed in the yards of residents' houses and several hamlet roads. Biopori infiltration hole technology in Sukanan Hamlet has benefits such as reducing the volume of organic waste, converting organic waste into compost, fertilizing the soil, reducing standing water, helping prevent flooding and improving ground water quality.